The Client Risk and The Audit Planning: Influence of Acceptance of Audit Engagement - Suryani, Deby; Sitorus, Tigor (International Research Journal of Business Studies, 2017)
This study briefly aims to extend the relationship between client risk with the audit planning by proposes the acceptance of auditengagement as mediate variable to fill a gap prior research, furthermore to determine the effect of client risk toward the audit planning. This research is a quantitative approach with primary data obtained by questionnaires. The population of this study are the auditors of Public Accounting Firm registered in the Directory Indonesian Institute of Accountants (Certified) 2016 in Jakarta and sample purposive about 197 respondents. The Structural Equation Modeling was used to analyze the data. The results of this research shows; (1). The Client Risk directly may affect on the audit planning in a positive but not significantly, (2). Client Risk directly affect the acceptance of audit engagement positively and significantly, (3). The Acceptance of audit engagement has positively and significantly influence on audit planning. Therefore the acceptance of audit engagement perfectly as mediating variable between client risk with the audit planning, where as the acceptance of audit engagement indicated by Time Budget Pressure, Audit Fee. Letter of Auditing and all indicator have a high loading factors.